PEGGUNAAN TEKNOLOGI DALAM MENINGKATKAN EFISIENSI BIAYA OPERASIONAL USAHA PENDIDIKAN - Dwi Indriyani Amiro; Tengku Maghfirah; Nurhasanaheni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study examines the role of information and communication technology in improving the operational efficiency of educational institutions, particularly in the areas of administration, academic services, and learning management. Through a qualitative approach based on a literature review of scientific sources from the past five years, it was found that the use of technologies such as Learning Management Systems (LMS), Academic Information Systems (SIAKAD), and cloud computing can automate processes, accelerate services, reduce costs, and improve data accuracy and transparency. However, challenges such as low digital literacy, infrastructure limitations, and resistance to change remain obstacles. Therefore, technology implementation must be carried out gradually, tailored to the institution’s readiness, accompanied by continuous training, and supported by government policies regarding infrastructure and regulations. These findings can serve as a reference in formulating effective and sustainable digital transformation strategies for education.